The Meaning Of Truth According To Pragmatism In The Context Of Christian Education - Pada, Miliani Selfina; Seran, Neri J.R; Eki, Mefi Osingra; Nubatonis, Miadi (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This article discusses the meaning of truth according to the school of pragmatism and its relevance in the context of Christian education. Pragmatism views truth as something that is evaluated based on its practical usefulness and its impact on real-life situations, rather than solely on theoretical conformity. In the field of education, particularly Christian education, this perspective is important because learning is not only aimed at the transfer of knowledge but also at shaping attitudes, character, and actions that reflect Christian values. This article employs a literature review approach by analyzing the thoughts of pragmatic philosophers alongside Christian theological principles. The findings indicate that although pragmatism emphasizes truth based on outcomes and benefits, Christian education must continue to place absolute truth, rooted in the Word of God, as its primary foundation. Therefore, pragmatic truth can be critically understood as a contextual tool in the learning process, as long as it remains directed toward the transformation of students’ lives in accordance with the teachings of Christ. This article is expected to contribute both theoretically and practically to the development of Christian Religious Education that is relevant, contextual, and grounded in Christian faith.